Prospective Observational Cohort Study of Tenecteplase Versus Alteplase in Routine Clinical Practice. Issue 12 (23rd September 2022) - Warach, Steven J.; Dula, Adrienne N.; Milling, Truman J.; Miller, Samantha; Allen, Leigh; Zuck, Nathan D.; Miller, Collin; Jesser, Christine A.; Misra, Lotika R.; Miley, Jefferson T.; Mawla, Manzure; Ding, Ming-Chieh; et al.
Abstract : Background: A 10-hospital regional network transitioned to tenecteplase as the standard of care stroke thrombolytic in September 2019 because of potential workflow advantages and reported noninferior clinical outcomes relative to alteplase in meta-analyses of randomized trials. We assessed whether tenecteplase use in routine clinical practice reduced thrombolytic workflow times with noninferior clinical outcomes. Methods: We designed a prospective registry-based observational, sequential cohort comparison of tenecteplase- (n=234) to alteplase-treated (n=354) stroke patients. We hypothesized: (1) an increase in the proportion of patients meeting target times for target door-to-needle time and transfer door-in-door-out time, and (2) noninferior favorable (discharge to home with independent ambulation) and unfavorable (symptomatic intracranial hemorrhage, in-hospital mortality or discharge to hospice) in the tenecteplase group. Total hospital cost associated with each treatment was also compared. Results: Target door-to-needle time within 45 minutes for all patients was superior for tenecteplase, 41% versus 29%; adjusted odds ratio, 1.85 (95% CI, 1.27–2.71); P =0.001; 58% versus 41% by Get With The Guidelines criteria. Target door-in-door-out time within 90 minutes was superior for tenecteplase 37% (15/43) versus 14% (9/65); adjusted odds ratio, 3.62 (95% CI, 1.30–10.74); P =0.02. Favorable outcome for tenecteplase fell within the 6.5% noninferiority margin; adjusted odds ratio, 1.26 (95% CI, 0.89–1.80). Unfavorable outcome was less for tenecteplase, 7.3% versus 11.9%, adjusted odds ratio, 0.77 (95% CI, 0.42–1.37) but did not fall within the prespecified 1% noninferior boundary. Net benefit (%favorable–%unfavorable) was greater for the tenecteplase sample: 37% versus 27%. P =0.02. Median cost per hospital encounter was less for tenecteplase cases (13 382 versus 15 841; P <0.001). Conclusions: Switching to tenecteplase in routine clinical practice in a 10-hospital network was associated with shorter door-to-needle time and door-in-door-out times, noninferior favorable clinical outcomes at discharge, and reduced hospital costs. Evaluation in larger, multicenter cohorts is recommended to determine if these observations generalize.